In-vitro evaluation of the effects of tigecycline on annulus fibrosus and nucleus pulposus (Annals of Medical Research, 2021)
Aim: This study aimed to examine the effects of tigecycline on primary cell cultures established using intervertebral disc tissues.Material and Methods: Primary Annulus Fibrosus and Nucleus Pulposus cultures were obtained from human intervertebral disc tissue. Untreated samples served as the control group, and treated samples served as the study group. Treated and untreated samples were statistically evaluated using an alpha significance value of 0.05.Results: Proliferation and gene expression decreased in the tigecycline administered cultures when compared to the control group samples (P 0.05). Conclusion: Drugs used in clinics may have side effects other than those indicated in their package insert.
Keywords: Chondroadherin gene; cartilage oligomatrix protein; interleukin-1beta; intervertebral disc cell culture; matrix metalloproteinase; tigecycline